POLICY IMPLEMENTATION OF THE RUMAH PENDIDIKAN PLATFORM IN THE GTK PORTAL BASED ON E-PERFORMANCE FOR PRIMARY SCHOOL PRINCIPALS IN CLUSTER II, NORTH ACEH DISTRICT - Yunitawati Yunitawati; Iis Marsithah; Alfi Syahrin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Digital transformation in the performance management of school principals has become part of the strategic policy of the Ministry of Education through the 331 Educational House Platform with the e-Performance-based GTK Room. This research aims to analyze the implementation of this policy, identify the operational steps applied in primary education units, and explore the supporting and inhibiting factors. This research applies a qualitative approach and uses a case study method in two public elementary schools located in North Aceh Regency. Data was collected through observations, in-depth interviews, and data collection. The results of the study show that the implementation of e-Performance is carried out through seven strategic stages: socialization, integration of GTK accounts, school program planning, platform-based implementation, utilization of the GTK Room, monitoring-evaluation, and follow-up and best practices. Main supporting factors include the visionary leadership of the school principal, human resource competencies, a collaborative organizational culture, adequate ICT infrastructure, technical training, and government regulations. On the other hand, implementation faces various obstacles such as low digital literacy, limited teacher competencies, technical system constraints, minimal direct technical support, and heavy workloads. This study concludes that the success of digital transformation based on e-Performance is greatly influenced by the synergy between the school's internal readiness and sustained external support. These findings provide empirical contributions to the development of digital policies in the basic education sector.